2011
DOI: 10.1021/je200921u
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Vapor–Liquid Equilibrium for Binary Systems of Toluene + Ethanol and Toluene + Isopropanol at (101.3, 121.3, 161.3, and 201.3) kPa

Abstract: VaporÀliquid equilibria (VLE) data for the toluene + ethanol and toluene + isopropanol binary systems have been measured at (101.3, 121.3, 161.3, and 201.3) kPa using a VLE recirculating still. The experimental data were checked with the Herington method, which showed thermodynamic consistency. The experimental VLE data were correlated with Wilson, nonrandom two-liquid (NRTL), and universal quasichemical (UNIQUAC) activity coefficient models. The results show that the calculated values of the vapor-phase mole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The values of the local optima solutions found were recorded and sorted by their quality (decreasing value of * ). Table 9 summarizes the best set of values that were found for the NRTL parameters of the systems under study x calc,i − x exp,i (10) for each water-IL and ethanol-IL binary systems and pressure datasets. In the T-x binary diagrams for the different ionic liquids in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of the local optima solutions found were recorded and sorted by their quality (decreasing value of * ). Table 9 summarizes the best set of values that were found for the NRTL parameters of the systems under study x calc,i − x exp,i (10) for each water-IL and ethanol-IL binary systems and pressure datasets. In the T-x binary diagrams for the different ionic liquids in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…an approximate total volume of the still of 120 cm 3 , requiring about 80 cm 3 of sample; Chen et al [10] used recirculation VLE still with internal volume of about 120 cm 3 of which the liquid occupied about 100 cm 3 . The VLE cell used by most researchers on this field such as Alvarez et al [7], Andreatta et al [11,12] and Calvar et al [5,13,14] is a glass Fischer Labodest equilibrium still that requires a sample volume of circa 35 cm 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For aqueous systems with a non volatile liquid compound the measurement of vapour liquid equilibrium is the most used, but in aqueous systems containing ionic liquids it is expensive and time consuming. Not only the available equipments, developed for conventional solvents, require a large sample volume ranging from the 250 cm 3 of Wang et al [36] down to the recently reported used of a glass Fischer Labodest equilibrium still that requires a sample volume of circa 35 cm 3 [37][38][39][40][41][42][43]. Moreover the high viscosity of the mixtures rich in ionic liquid difficult a regular boiling of the mixture, what causes long equilibration times, easily reaching 6 h. To overcome these limitations we have recently reported a microebulliometer of just 8 cm 3 of capacity to study these systems [44].…”
Section: Introductionmentioning
confidence: 99%
“…This obvious similarity strongly suggests that the polar solvent (isopropyl alcohol) needed to induce dissolution of the SBI evaporates early during the drying process, thereby allowing the nanostructure to be templated by the remaining nonpolar solvent (toluene). (We note here that the TIPA mixed solvent is reported to exhibit complex liquid‐vapor equilibria, including the existence of an azeotrope.) A contrast‐reversed series of 2‐D slices extracted from a 3‐D TEMT reconstruction of this morphology at depths of 10, 20, and 30 nm is presented in Figure and, along with previously reported 3‐D TEMT images, confirms that the ion‐rich microdomains are largely discontinuous, which is not a favorable spatial arrangement by which to promote ion diffusion.…”
Section: Resultsmentioning
confidence: 80%